Voluntary Corporate Governance Disclosure Innovative Evidence: The Case of Jordan - Awwad Almanasir, Ahmad Hamed; Shivaraj, B. (Journal of Reviews on Global Economics, 2017)
This paper aimed to assess the corporate governance voluntary disclosure level and the impact of a set of corporate governances (CG) attributes on the level to which corporate governance voluntary disclosure is conducted in Jordan. Another objective was to determine if Jordanian industrial listed corporations adhere to and disclose good CG practices voluntarily, and if they do, to determine the factors influencing such disclosure. This study employed 61 industrial listed firms for the years 2010-2014. The research developed a general voluntary CG disclosure index composing of 15 Jordanian Corporate Governance Codes and gauged the relationship via pooled OLS and regression method. The results indicated that the proposed Jordanian Corporate Governance Index (JCGI) enhanced voluntary corporate governance disclosure among Jordanian listed firms over the examined years. They also showed varying levels of CG disclosures in different scenarios; 1) it is lower in firms with higher managerial ownership and 2) higher relative to the independent directors’ proportion on the board, audit firm size, and audit committee presence with institutional ownership. Evidence on the compliance level towards the CG code in Amman Stock Exchange is unique and the study is distinct as it provides a pioneering evidence of the achieved compliance level.